ANALYSIS OF PHYSICAL COMPONENTS IN WRESTLING FREESTYLE - Eko Nur Cahyono; Widiastuti; Hernawan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
Abstract The purpose of this study was to determine the effect of arm power, agility and eye-hand and foot coordination in performing arm slamming skills in wrestling athletes in West Java Province. The population that was reached in this study were all wrestling athletes in the West Java area, which consisted of 30 freestyle wrestling athletes. Determination of the sample using a saturated sample, meaning that the entire affordable population is used as a research sample. The data analysis technique used is descriptive analysis and path analysis with the help of SPSS version 21 computer program with a significant level of 95% or = 0.05. The results showed that: The direct effect given by the arm power variable (X1) on the eye, hand and foot coordination variable (X3) was -0.414. Then the direct effect given by the agility variable (X2) on the eye, hand and foot coordination variable (X3) is -0.357. Then the direct effect given by the arm power variable (X1) on the arm swing skill variable (Y) is 0.546. Then the direct effect given by the agility variable (X2) on the arm swing skill variable (Y) is 0.638. And lastly, the direct effect given by the eye, hand and foot coordination variable (X3) on the arm slamming skill variable (Y) is 0.351. Sobel test calculations (Sobel Test) obtained that the value of one-tailed probability (One-tailed probability) of 0.029 <0.05. So it can be concluded that the arm power variable (X1) has an indirect effect through eye coordination, hands and feet (X3) against arm slam skills (Y). Then the results of the Sobel test calculation (Sobel Test) obtained that the one-tailed probability value is 0.0730 > 0.05. So it can be concluded that the agility variable (X2) has no indirect effect through eye, hand and foot coordination (X3) on arm slamming skills (Y). Keywords: Arm Power, Agility, Eye, Hand and Foot Coordination, Arm Kick Skills, Wrestling